2019
DOI: 10.3389/fnins.2018.01020
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Homeostasis Is Not Affected in a Murine Model of Parkinson’s Disease Induced by 6-OHDA

Abstract: There is a mutual relationship between metabolic and neurodegenerative diseases. However, the causal relationship in this crosstalk is unclear and whether Parkinson’s disease (PD) causes a posterior impact on metabolism remains unknown. Considering that, this study aimed to evaluate the appearance of possible changes in metabolic homeostasis due to 6-hydroxydopamine (6-OHDA) administration, a neurotoxin that damage dopaminergic neurons leading to motor impairments that resemble the ones observed in PD. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Gomes et al (2019) given 20 µg of 6-OHDA in 3 µL (in saline and ascorbic acid) bilaterally into dorsolateral striatum to induce the neurodegeneration in male Wistar rats and assessed the motor and metabolic outcomes on the 7th, 21st, or 35th day after 6-OHDA lesion. The motor abnormalities paralleled without a noteworthy change in body mass, food consumption, glucose tolerance, insulin sensitivity, and other biochemical parameters (such as plasma insulin levels, triacylglycerol, and total cholesterol levels) [ 107 ]. Voronin et al 2019 in their study, administered 5 µg of 6-OHDA in 1 µL (saline and ascorbic acid at 0.5 µL/min) intrastriatal (into right striatum) and evaluated the effect of afobazole (2.5 mg/kg, intraperitoneally) in 6-OHDA-lesioned male CD-1 mice model.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…Gomes et al (2019) given 20 µg of 6-OHDA in 3 µL (in saline and ascorbic acid) bilaterally into dorsolateral striatum to induce the neurodegeneration in male Wistar rats and assessed the motor and metabolic outcomes on the 7th, 21st, or 35th day after 6-OHDA lesion. The motor abnormalities paralleled without a noteworthy change in body mass, food consumption, glucose tolerance, insulin sensitivity, and other biochemical parameters (such as plasma insulin levels, triacylglycerol, and total cholesterol levels) [ 107 ]. Voronin et al 2019 in their study, administered 5 µg of 6-OHDA in 1 µL (saline and ascorbic acid at 0.5 µL/min) intrastriatal (into right striatum) and evaluated the effect of afobazole (2.5 mg/kg, intraperitoneally) in 6-OHDA-lesioned male CD-1 mice model.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…When analyzing the impact of 6-OHDA on cholesterol concentrations, a study employing bilateral brain injection found no significant differences in plasma cholesterol levels between parkinsonian rats and control counterparts. Conversely, another study using unilateral 6-OHDA-induced lesion showed reduced concentrations of cholesterol ester in the cerebrospinal fluid of rats [35,36].…”
Section: Discussionmentioning
confidence: 90%
“…According to an earlier study, rotenone treatment did not cause an increase in blood glucose 39 . But, treatment with rotenone increased blood glucose in the present study; though the increase was never beyond the 95th centile value for FBS/PBS of Wistar rats (95% upper limit was 6.2 mmol/L and 7.9 mmol/L, respectively) 40 .…”
Section: Urea Changes In Thementioning
confidence: 88%